The Vietnam cookbook : thom ngon - The Asian Testkitchen; Leilani Lee (Wilmington : Mindful Publishing, 2020)
Many traditional recipes can be found in our cookbooks, but also modernized ones. Since it is often the case that you can't get all the ingredients for a recipe in the vicinity, we have modified some recipes with similar ingredients that achieve the same result, but can definitely be recooked without spending a lot of money on the ingredients and without having to search for them.
Keywords: Vietnam Cookbook; Vietnamese Cuisine